Factors Influencing Hedging Decisions Of Mining Sector Companies Listed On The Indonesia Stock Exchange 2014 – 2018 - Ning Aini Lathifah; H. Muhammad Ali; Mursalim Nohong (Citakonsultindo, 2023)
This study aims to determine the effect of liquidity (current ratio) and profitability (return on asset) on hedging decisions in mining companies in the Indonesia Stock Exchange 2014-2018 period. The total population in this study were 51 mining companies listed on the Indonesia Stock Exchange in the 2014-2018 period. There were 35 companies that met the criteria to be sampled in this study. Data collections were conducted by non-participant observation method, namely through financial report data published on the website www.idx.co.id. The analysis technique used in this study is logistic regression analysis. The results of hypothesis testing show that the liquidity which proxied by current ratio has negative, insignificant influence on hedging decision. and the profitability proxied by return on asset has significance and positive influence on hedging decisions.